The Oxygenated Drinking Water - Erwana Dewi (Politeknik Negeri Sriwijaya, 2022)
Oxygen is an essential substance for humans, available in the air and can be freely enjoyed. At present, oxygen is not only supplied through the respiratory system, but is also supplied through the digestive system. The alternative is to supply oxygen through drinking water. In this research the design process will be carried out to produce drinking water that contains oxygen, or oxygenated drinking water. The process to make drinking water by using the membrane RO (Reverse Osmosis) and the processed by injecting oxygen using Aquatic Oxygenator. In the procesess of the RO membran and the Aquatic Oxygenator has oxygen as 100 ppm optimum in drinking water. The effect of oxygenization time and temperature on oxygen levels is the dissolved oxygen content in drinking water does not increase significantly, only in the range of 100-113.4 ppm. When the oxygenization temperature increases, the solubility of oxygen in water decreases. The effect of drinking water volume and oxygenation time on dissolved oxygen levels in water the dissolved oxygen level reaches 100 ppm, and continues with oxygenation, the measurement number does not change.